PELAKSANAAN MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN EFEKTIFITAS PEMBELAJARAN PAI SISWA DI SD NURUL AMIN ISLAMIC SCHOOL BEKASI - Susilawati, Susilawati; Ferianto, Ferianto (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2023)
This study aims to determine the description of the management of facilities and infrastructure carried out at SD Nurul Amin Islamic School Bekasi in order to increase the effectiveness of students' Pai learning. This method uses qualitative research. That is to describe descriptively the implementation of facilities and infrastructure management in increasing the effectiveness of Pai learning at SD Nurul Amin Islamic School Bekasi. Data collection techniques are by observation and interviews. Management facilities and infrastructure in learning pie must be managed properly. Because if the management is right, it will result in the effectiveness of Pai learning. The management of facilities and infrastructure carried out at SD Nurul Amin Islamic School Bekasi such as planning for facilities and infrastructure, procurement, storage, distribution, maintenance and rehabilitation of facilities and infrastructure are carried out properly and appropriately. With the precise implementation of facilities and infrastructure management at SD Nurul Amin Islamic School Bekasi, Pai learning runs effectively so that student scores can increase and students can also compete with students in other schools by participating in several competitions such as calligraphy, memorizing the Qur'an and speeches